2009
DOI: 10.1016/j.jalz.2009.05.667
|View full text |Cite
|
Sign up to set email alerts
|

Scales as outcome measures for Alzheimer's disease

Abstract: The assessment of patient outcomes in clinical trials of new therapeutics for Alzheimer's disease (AD) continues to evolve. In addition to assessing drugs for symptomatic relief, an increasing number of trials are focusing on potential disease-modifying agents. Moreover, participants with AD are being studied earlier in their course of disease. As a result, the limitations of current outcome measures have become more apparent, as has the need for better instruments. In recognition of the need to review and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 107 publications
2
41
0
1
Order By: Relevance
“…these observations are in line with recent publications that bring into question the sensitivity of adascog in mild cognitive impairment and mild ad (17)(18)(19). this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17). Furthermore, several recent studies have reported slower rates of placebo decline in ad patients than traditionally assumed by older models and clinical trials (12,(21)(22)(23); they have also shown that baseline adas-cog significantly affects the rate of ad progression (23,24).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of supporting
confidence: 93%
See 1 more Smart Citation
“…these observations are in line with recent publications that bring into question the sensitivity of adascog in mild cognitive impairment and mild ad (17)(18)(19). this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17). Furthermore, several recent studies have reported slower rates of placebo decline in ad patients than traditionally assumed by older models and clinical trials (12,(21)(22)(23); they have also shown that baseline adas-cog significantly affects the rate of ad progression (23,24).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of supporting
confidence: 93%
“…Within the group of patients with higher adas-cog scores at baseline, souvenaid significantly improved adas-cog scores compared with the control group. these observations are in line with recent publications that bring into question the sensitivity of adascog in mild cognitive impairment and mild ad (17)(18)(19). this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of supporting
confidence: 87%
“…Instead, these effects have been modelled via intermediate outcomes given some critical assumptions on their relationship with the outcomes of interest [26]. Nevertheless, the effect on institutionalization appears difficult to validate as shown in the AD2000 study [35,36]. Differences in the availability of institutions across countries further increase the complexity of this outcome, as the relationship between dementia symptoms and institutionalization, therefore, likely varies across countries and contexts.…”
Section: Long-term Cost-effectiveness Is Uncertain When Extrapolatingmentioning
confidence: 99%
“…As noted earlier, ADAS-cog is usually the preferred primary cognitive end point in clinical trials in mild-to-moderate AD [47], but it has ceiling and floor effects making it less suitable in early and late stages of AD [35]. In moderate-to-severe AD, the Severe Impairment Battery [54] may be better suited, whereas in early AD, the Repeatable Battery for the Assessment of Neuropsychological Status [55] has been suggested [35]. The availability of data has caused many models to use the screening tool Mini-Mental State Examination (MMSE) [56] to represent cognitive decline.…”
Section: Instruments In Different Stages Of Diseasementioning
confidence: 99%
“…Over recent years, questions have been raised regarding the suitability of the ADAS-Cog to assess those with mild AD [6][7][8] . These questions cover three main issues; the appropriateness of the cognitive domains tested, the psychometric properties and the variability in administration and scoring of the ADAS-Cog.…”
Section: Short Communicationmentioning
confidence: 99%